Ask Question
29 July, 06:47

Use function notation to write a recursive formula to represent the sequence: 3, 6, 12, ...

f (n) = f (n - 1) + 3

f (n) = f (n - 1) + 2

f (n) = f (n-1).3

f (n) = f (n-1) 2

+5
Answers (1)
  1. 29 July, 07:12
    0
    f (n) = f (n-1) * 2

    Step-by-step explanation:

    The previous term is being multiplied by 2 to get a term.

    First term is 3.

    Second term is 3*2=6.

    Third term is 6*2=12.

    ...

    nth term is f (n-1) * 2.

    Note: f (n-1) is just the term before f (n).

    f (n) = f (n-1) * 2 with f (1) = 3 is the recursive form for this sequence.
Know the Answer?
Not Sure About the Answer?
Find an answer to your question 👍 “Use function notation to write a recursive formula to represent the sequence: 3, 6, 12, ... f (n) = f (n - 1) + 3 f (n) = f (n - 1) + 2 f ...” in 📗 Mathematics if the answers seem to be not correct or there’s no answer. Try a smart search to find answers to similar questions.
Search for Other Answers